Tokyo Ghoul [root] A. Season 2 [videorecording (DVD)] - Morita, Shūhei (FUNimation Productions, 2016)
Kaneki joins Aogiri Tree just as a war erupts between ghoul factions, while Amon and Akira lead the anti-ghoul attacks.